PENGGUNAAN MIXED CULTURE JAMUR DAN PENAMBAHAN SUMBER N PADA BIODEGRADASI TANDAN KOSONG KELAPA SAWIT DALAM PENGKOMPOSAN - Latarus Fangohoi; Agustina Agustina; Lisa Navitasari (BUANA SAINS, 2014)
Oil palm empty fruit bunches (EFB) is the largest solid waste palm oil production. The waste pollutes the environment and waste management (EFB) has been carried out with burnt, aggravating environmental pollution. This resulted in the need for environmentally-friendly waste management. One of them uses microbes that can degrade components of the waste so that the waste can be used as compost EFB and natural mulch for agriculture. Use of microbes to degrade the waste components EFB potentially produces enzymes that accelerate the degradation lignoselulolitik EFB waste components. This research aims to study the biodegradation by a mixture of isolates of Aspergillus sp., Trichoderma sp. and Actinomycetes with the addition of some nitrogen as a nutrient source for growth microbes. The results showed that the addition of a mixture of isolates with the addition amoniumsulfat and chicken manure as a source of N can lower C / N ratio of 10 and 51.9 % of fragility, as well as lower levels of cellulose, hemicellulose and lignin respectively 66 %, 36.4 % and 40.7 % of the initial levels. These results indicate that the addition of N sources of natural and synthetic amoniumsulfat chicken manure as well as accelerate the degradation of fungal isolates TKKS into compost